Bowo Perkawinan Adat Suku Nias Dengan Dasar Perkawinan Gereja Katolik - Kristiana Mendrofa (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Böwö marriage of the Nias tribe is generally interpreted as sumange (giving awards). Böwö is masi-masi/hele-hele dödö Zatua khö nono nia ono alawe (giving affection/proof of the bride's parents' love at the time of marriage). Böwö determines the agreement for the implementation of a marriage. This can take the form of money, gold and other trinkets. The aim is as a form of humanizing humans through love and living prosperously in the family. However, the current application of Böwö is contrary to the true meaning of Böwö. Recently, Böwö in Nias society has experienced a change in meaning and even received a meaning that is contrary to its true meaning. There is a decline in Böwö's understanding which leads to a materialistic aspect. Böwö became honest too expensive. Therefore, it is necessary to investigate why there is a change in the implementation of Böwö. This research specifically seeks to determine the understanding of Böwö Nias ethnic marriages on the basis of Catholic Church marriages using qualitative research which uses three data collection techniques, namely, observation, interviews and documentation. From the researcher's observations, it was found that the Böwö marriage of the Nias tribe is known and is still carried out in social life. Through interviews with informants, researchers found that in the implementation of the Böwö traditional Nias marriage, its meaning had decreased. The reality on the ground shows that some Nias people experience poverty because Böwö is too expensive. Böwö is no longer an expression of love. The informants wanted Böwö to be restored to its true meaning as masi-masi (proof of love). For this reason, it is necessary to simplify Böwö on the basis of Catholic Church marriage. This needs to be socialized to Catholics so that they truly understand and are able to practice it according to the true meaning of Böwö.